Building Inclusive Empathetic Learning Environments through Emotional Intelligence Practices among Teachers in Diverse Educational Contexts - Sarbaini, Sarbaini; Timothy, Hendrawan; Hesline Palandi, Esther; Probosari, Ninik; Hamzah, Muh. Zuhdy (Mandalika: Jurnal Ilmu Pendidikan dan Bahasa, 2026)
This study aims to analyze how emotional intelligence (EI) practices among teachers contribute to fostering inclusive and empathetic learning environments within diverse educational contexts. Employing a qualitative library research design, the study systematically reviews and synthesizes scholarly literature from peer-reviewed journal articles, academic books, and institutional reports related to emotional intelligence, empathy, and inclusive education. The analysis focuses on teachers’ emotional competencies—particularly self-awareness, self-regulation, empathy, and social skills—and their contribution to addressing students’ diverse emotional and cultural needs. The findings reveal that emotionally intelligent teachers are more capable of creating inclusive classroom climates that promote equity, respect diversity, and support students’ socio-emotional development. Furthermore, the study identifies empathy-driven pedagogy, reflective practices, and adaptive communication as key mechanisms through which EI is translated into effective teaching practices. These approaches enable teachers to build meaningful relationships with students and foster a sense of belonging in the classroom. The study also highlights the importance of integrating EI frameworks into teacher professional development programs to enhance responsiveness and inclusivity. The findings indicate that emotional intelligence functions not only as an individual competence, but also as a pedagogical foundation for strengthening inclusive education and improving students’ well-being. Ultimately, cultivating emotionally intelligent educators is essential for creating learning environments where all students feel recognized, supported, and empowered, thereby promoting more equitable and compassionate education systems.